The impact of credit services Antique Cooperatives provide on the socio-economic status of their members - Baldevia, Joanne; Barte, Rhenozo; Gayagaya, Pearl Joy; Puga, Baby Amelia; Obejuela, Johanna
This study is an assessment of the impact of Antique cooperatives in general. However, the scope of such topic is so broad that really compelled the researchers to streamline it for fear that, because of insufficient data available, the needed outcome ,might not precisely be achieved. The study was redirected and was focused more on the more specific field on which the impact could be more determined well. The study is concentrated more, but not all, on the impact on socio-economic aspect of the members. The study was made to determine whether the economic status of coop members improved to have a basis in knowing whether the impact is favorable or unfavorable. Related to this, is the aim to know the cause and effect relationship between the members' social and economic life. Another is to know the degree of reliance members put on their coop. After knowing all of these things, it is then easier to know whether the impact brought about improvement in the standard of living of the members in general. A survey was conducted in selected Cooperatives in Antique. The respondents were all members of cooperatives. In choosing them, no particular consideration was given to the specific assignments or responsibilities they have on their respective coop. Aside from the questionnaires used in gathering information, personal interviews were also conducted to substantiate the information needed for the conclusions or whatever generalizations that are expected to be made after some analyses. The researchers took time in gathering data in Antique. Letters were given to selected cooperatives, asking for their permission to conduct a survey. After their approval, the initiative of distributing the questionnaires vested on the researches. They were given out at random. Some questionnaires were distributed from house to house some were distributed in the offices of the Cooperatives. Data were processed by tabulating the frequencies and the corresponding percentages of the answers. Data gathering for the interview method, ws done by going to the Coop Office and conduct an interview with the officers and staff. Interview with the members was minimal since survey forms was already determined substantial to get their views. It was found out that financial problem has a bearing on the social life of coop members. The question posed to get the social problems boil down to the individual person which compose the society. One may feel terribly incapacitated because ot the absence of money. Shame may also be experienced. All these reveal that financial stability, although not the only factor, determines social improvement. The survey also revealed that coop made a positive impact by bringing up the average daily gross income of the members. They get money from the cooperatives to start off a business, be educated, buy basic needs, finance unexpected need, maintain good health, etc. Members were also able to acquire several properties through their membership in coop. After the processing, presentation, and analysis of data gathered, though at first glance, it can be deduced that cooperatives made a wholesome impact on their members' lives, certain points have also been identified on which cooperatives can still exert much effort. That would facilitate a more effective and efficient rendetion of service to their members. The recommendations hinted at include the participation of the government in the undertakings of cooperative. It is also suggested that members should realize the importance of their participation and cooperation some more. The coop management is also encouraged to involve their members some more in their activities, and they should elicit positive suggestions from them for improvement.